If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + 6) + 3y = 5 Reorder the terms: 2(6 + 2y) + 3y = 5 (6 * 2 + 2y * 2) + 3y = 5 (12 + 4y) + 3y = 5 Combine like terms: 4y + 3y = 7y 12 + 7y = 5 Solving 12 + 7y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7y = 5 + -12 Combine like terms: 12 + -12 = 0 0 + 7y = 5 + -12 7y = 5 + -12 Combine like terms: 5 + -12 = -7 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| -24+4b=20 | | 12th=-132 | | m+412=1000 | | -5(x+3)-10=13+2 | | dt=3(d+w) | | 2u+6=5u-3 | | -87+7x=-4x+122 | | x+(2x-60)=180 | | x-4-3x=-3-1 | | 110x=150+85x | | 6x*6x^3= | | 6y=10-4x | | -5(x+3)-10=13+3 | | x+x(.22)=x+5.5 | | -3k-8=1 | | -52=-4f | | 20-2=-4 | | 131=5x+41 | | 8z-z=3+2z-3-9 | | 0.5*30= | | 5a-4(a-8)=13+2a | | 18x-20=15x | | 2x+3+5x=-11 | | 10x-4+144=180 | | 3u+3v=15 | | x+2(x-7)=5x-3 | | 5(6x+3)=4x+2 | | 4xn=196 | | 6(6x+3)=4x+2 | | 5u-3u=5-3u | | 9x-4+85=180 | | -3=x-7-2x |